Staphylococcal enterotoxins bind H-2Db molecules on macrophages. - Beharka, A A (1995)
We screened a panel of monoclonal antibodies against selected macrophage cell surface molecules for their ability to inhibit enterotoxin binding to major histocompatibility complex class II-negative C2D (H-2b) macrophages. Two monoclonal antibodies, HB36 and TIB126, that are specific for the alpha 2 domain of major histocompatibility complex class I, blocked staphylococcal enterotoxins A and B (SEA and SEB, respectively) binding to C2D macrophages in a specific and concentration-dependent manner. Inhibitory activities were haplotype-specific in that SEA and SEB binding to H-2k or H-2d macrophages was not inhibited by either monoclonal antibody. HB36, but not TIB126, inhibited enterotoxin-induced secretion of cytokines by H-2b macrophages. Lastly, passive protection of D-galactosamine-sensitized C2D mice by injection with HB36 antibody prevented SEB-induced death. Therefore, SEA and SEB binding to the alpha 2 domain of the H-2Db molecule induces biological activity and has physiological consequences.